Association Between Diabetic Retinopathy and Body Mass Index - Saleem, Wishal; Khan, Mutaish Arif; Khan, Awais Ahmad; Shah, Masood Alam (Biological and Clinical Sciences Research Journal, 2025)
Diabetic retinopathy is a leading microvascular complication of type 2 diabetes mellitus and a major cause of vision loss. Obesity, assessed through body mass index, contributes to insulin resistance and chronic inflammation, potentially increasing the risk and progression of diabetic retinopathy. Understanding this relationship is essential for early detection and prevention, especially in populations like Pakistan, where obesity and diabetes are increasingly prevalent. Objective: To determine the association between body mass index and diabetic retinopathy in patients with type 2 diabetes mellitus presenting to the Ophthalmology Unit of Ayub Teaching Hospital, Abbottabad, from November 2024 to April 2025. Methods: A cross-sectional study was conducted over 6 months among 196 patients with type 2 diabetes mellitus, selected using consecutive sampling. Demographic, clinical, and biochemical data were collected along with fundoscopic evaluation using slit lamp biomicroscopy. Body mass index was calculated and categorized per World Health Organization criteria. Diabetic retinopathy was staged using standard clinical definitions. Data were analysed in SPSS version 20 using descriptive statistics and chi-square tests to assess associations, with p < 0.05 considered significant. Results: Participants had a mean age of 57.6 ± 9.1 years, and females represented 52 percent of the sample. Most patients belonged to middle socioeconomic strata and rural backgrounds. The mean duration of diabetes was 8.2 ± 4.5 years, while the mean HbA1c was 8.9 ± 1.4 percent. The mean BMI was 28.7 ± 3.9 kg/m², with overweight (40.3 percent) and obese (24.5 percent) groups constituting the majority. Diabetic retinopathy was identified in 68.9 percent of patients, with 28.6 percent having non proliferative disease and 16.3 percent having proliferative retinopathy. A statistically significant association was observed between increasing BMI and the severity of diabetic retinopathy (p = 0.03), with proliferative disease being highest among obese individuals (29.2 percent). Conclusion: Higher BMI was significantly associated with more advanced stages of diabetic retinopathy in patients with type 2 diabetes mellitus. These findings highlight obesity as a modifiable risk factor that should be targeted through preventive measures, patient education, and early retinal screening to reduce visual morbidity.